Media Sosial sebagai Alat Dakwah: Analisis Video YouTube Ustadzah Halimah Alaydrus tentang Pencegahan Bunuh Diri - Mukarromah, Faizatul; Nurdin, Ali (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2024)
AbstractSuicide is a serious problem that occurs among women, caused by depression, disappointment and pressure from the social environment. Ustadzah Halimah Alaydrus is an Islamic preacher who fights for women's rights not to commit suicide, through the YouTube platform. This research aims to analyze Ustadzah Halimah Alaydrus's message in the YouTube video